Lampungnese Anger Intonation - Reranta, Redika Cindra (TEKNOSASTIK, 2024)
Misinterpretation of intonation can generate communication difficulties or even problems. Non-native speakers frequently mistook Lampungnese neutral speech uttered by native speakers for rage speech, as one example of misunderstanding tone. The purpose of this study was to find a solution to the problem. The IPO approach was used in this work, with three key activities: speech generation, speech acoustic analysis, and perceptual test experiments. The data consisted of segmentally similar recordings of Lampungnese neutral and angry speech. The utterance was made up of three sentence patterns that were each repeated four times by four native speakers. Furthermore, the data were examined to determine the acoustic difference between the two speeches as well as the acoustic parameter that gave the Lampungnese neutral speech an angry perception. The results of the investigation revealed that Lampungnese neutral and angry speech were distinguishable by pitch, with angry speech having a higher pitch. Following that, two tests were conducted: (1) raising the pitch of Lampungnese neutral intonation and (2) reducing the pitch of Lampungnese rage intonation. Finally, the experimental results revealed that pitch is the acoustic characteristic that represents the speaker's anger emotion. According to the findings, higher pitch implies the angry emotion.Keywords: anger, acoustic utterance, Lampungnese.